2002
DOI: 10.1029/2001jc000900
|View full text |Cite
|
Sign up to set email alerts
|

Wind stress forcing of the Oregon coastal ocean during the 1999 upwelling season

Abstract: [1] The wind stress forcing of the Oregon coastal ocean during June -August 1999 is estimated from a regional mesoscale atmospheric model and from satellite scatterometer observations, supplemented by moored and coastal surface data and by a land-based wind profiler. Both the mean and variable components of model alongshore wind stress increase by factors of 3 -4 from north to south along the Oregon coast. There is evidence of orographic intensification near Cape Blanco, which is supported by previous aircraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 16 publications
6
57
0
Order By: Relevance
“…At offshore locations, the vertical velocity at the base of the surface layer induced by Ekman pumping is proportional to the curl of the wind stress (w D ϭ curl /( f) ϭ ‫ץ(‬ y /‫ץ‬x Ϫ ‫ץ‬ x /‫ץ‬y)/( f ), where is the wind stress vector, x and y are its eastward and northward components, and is the water density). High resolution estimates of the wind stress in this region can be obtained from the SeaWinds scatterometer onboard the NASA QuikSCAT satellite launched in July 1999 (Samelson et al, 2002;Perlin et al, 2004). The QuikSCAT orbit provides twice-daily coverage at about 0300 UTC and 1400 UTC; summer observations are available for four years (2000 -2003); results are interpolated onto a 0.25°grid (Ϸ 25 km).…”
Section: [63 5 Journal Of Marine Research a Wind Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…At offshore locations, the vertical velocity at the base of the surface layer induced by Ekman pumping is proportional to the curl of the wind stress (w D ϭ curl /( f) ϭ ‫ץ(‬ y /‫ץ‬x Ϫ ‫ץ‬ x /‫ץ‬y)/( f ), where is the wind stress vector, x and y are its eastward and northward components, and is the water density). High resolution estimates of the wind stress in this region can be obtained from the SeaWinds scatterometer onboard the NASA QuikSCAT satellite launched in July 1999 (Samelson et al, 2002;Perlin et al, 2004). The QuikSCAT orbit provides twice-daily coverage at about 0300 UTC and 1400 UTC; summer observations are available for four years (2000 -2003); results are interpolated onto a 0.25°grid (Ϸ 25 km).…”
Section: [63 5 Journal Of Marine Research a Wind Forcingmentioning
confidence: 99%
“…Gan et al (2005) have recently modeled the response of this coastal ocean to wind forcing from a regional atmospheric model. Samelson et al (2002) showed that the atmospheric model wind stress fields generally resemble QuikSCAT fields (see their Figs. 2 and 5): both show much stronger alongshore wind stress at 42N than at 45 and 47N, though details of the gradients in the lee of Cape Blanco differ.…”
mentioning
confidence: 99%
“…Station NWP03, located on the south jetty of the Newport harbor entrance (Fig. 2), is representative of nearshore winds throughout the study area during summer (Kirincich et al 2005;Samelson et al 2002). Wind stress was calculated following Large and Pond (1981), assuming neutral stability.…”
Section: A Data Sourcesmentioning
confidence: 99%
“…There was no difference between the start of upwelling calculated from yearly dates and wind climatology in Region E. This was due to the more steady southward direction of the winds in this area throughout the spring and summer. There is a change in wind, and hence upwelling, climatology around Cape Blanco (42.84°N, between the coastal Regions D and E; Samelson et al 2002, Huyer et al 2005, Venegas et al 2008. North of Cape Blanco there was no significant difference in the timing of the upwelling season, but south of Cape Blanco upwelling favorable winds started significantly earlier and finished significantly later.…”
Section: Physical Oceanographymentioning
confidence: 91%
“…upwelling favorable winds occur after late February each year. A latitudinal gradient in winds and in the onset and intensity of upwelling has been noted for the California Current System (Strub et al 1987a,b, Largier et al 1993, Strub & James 2000, Samelson et al 2002, but previous studies have not looked in detail at the Oregon coast and thus have potentially missed smaller-scale spatial patterns.…”
Section: Physical Oceanographymentioning
confidence: 99%